Fatty Liver Disease - Liver Care With Multidimensional Approach (Homoeopathy for All, 2024)
Fatty liver, also known as fatty  liver disease (FLD), is a  reversible condition where  large vacuoles of triglyceride fat  accumulate in liver cells via the  process of steatosis (i.e. abnormal  retention of lipids within a cell). The  liver is the largest gland in the body  situated below the diaphragm, on the  right side of the abdomen and has  many vital functions to perform for  the body. It filters the blood coming  from the digestive tract before it  passes to the body. Other important  functions of the liver are metabolism  of carbohydrates, proteins, lipids and  amino acids in the body; production  of bile that help in breaking down the  fat and detoxification of chemicals  and drugs. Its other functions include  producing blood clotting factors,  storage of glucose and clearance of  bilirubin. In this article we discuss  about the major factor that affects  the normal functioning of liver –  Non Alcoholic liver disease.
Keywords: nonalcoholic; alcohol; accumulate